Mechanistic insights into the inhibition of endo-beta 1,4 xyloglucan hydrolase by a classical aspartic protease inhibitor - Menon, Vishnu; Rao, Mala (Journal of Fluorescence, 2013)
This is the first report of inactivation of xyloglucanase from Thermomonospora sp by pepstatin A, a specific inhibitor towards aspartic proteases. The steady state kinetics revealed a reversible, competitive, two-step inhibition mechanism with IC (50) and K (i) values of 3.5 +/- 0.5 mu M and 1.25 +/- 0.5 mu M respectively. The rate constants determined for the isomerization of EI to EI* and the dissociation of EI* were 14.5 +/- 1.5 x 10(-5) s(-1) and 2.85 +/- 1.2 x 10(-8) s(-1) respectively, whereas the overall inhibition constant K (i) (*) was 27 +/- 1 nM. The conformational changes induced upon inhibitor binding to xyloglucanase were monitored by fluorescence analysis and the rate constants derived were in agreement with the kinetic data. The abolished isoindole fluorescence of o-phthalaldehyde (OPTA)-labeled xyloglucanase and far UV analysis suggested that pepstatin binds to the active site of the enzyme. Our results revealed that the inactivation of xyloglucanase is due to the interference in the electronic microenvironment and disruption of the hydrogen-bonding network between the essential histidine and other residues involved in catalysis.
Keywords: 4 xyloglucan hydrolase; Endo-beta 1; Enzyme kinetics; Inactivation mechanism; Pepstatin; Slow-tight binding